The sedentary behavior reduction in pregnancy intervention (SPRING) pilot and feasibility randomized trial - Bethany Barone Gibbs; Andrea C. Kozai; Shannon N. McAdoo; Kelliann D. Davis; Meghan B. Savidge; Joshua L. Paley; Alisse Hauspurg; Janet M. Catov (BMC, 2024)
Abstract Pregnant individuals rarely achieve moderate-to-vigorous intensity physical activity recommendations. Purpose The sedentary behavior reduction in pregnancy intervention (SPRING) pilot and feasibility randomized trial aimed to demonstrate feasibility, acceptability, and initial efficacy of a lower intensity intervention targeting reduced sedentary behavior and increased standing and steps. Methods First trimester pregnant individuals at risk for high sedentary behavior and adverse pregnancy outcomes (APO) were randomized 2:1 to a multi-component sedentary behavior reduction intervention or no-contact control. Intervention components included biweekly remote health coaching, wearable activity monitor, height-adjustable workstation, and a private Facebook group. Evidence-based behavioral targets included sedentary time < 9 h/day, increasing standing by 2-3 h/day, and ≥ 7500 steps/day. Participants completed all-remote assessments (baseline, second trimester, third trimester) of sedentary behavior and activity (thigh-worn activPAL) along with exploratory pregnancy health outcomes abstracted from medical records. Intervention effects vs. control were evaluated using generalized mixed models and an intention-to-treat approach. Intervention participants also provided feedback on perceived benefits and acceptability. Results Participants (34 intervention; 17 control) had mean age 32 years, were 83% White, with mean pre-pregnancy BMI 28 kg/m2. Retention was high (90% and 83% at second and third trimester follow-up visits). Intervention participants decreased sedentary time (-0.84 h/day, p = 0.019) and increased standing (+0.77 h/day, p = 0.003), but did not increase steps/day (+710, p = 0.257) compared to controls. Intervention participants reported many perceived benefits and identified the wearable, height-adjustable workstation, and behavioral lessons as most useful. Conclusion For pregnant individuals at risk for high sedentary behavior and APOs, a sedentary behavior reduction intervention is feasible, acceptable, and may offer a viable alternative to more intense physical activity recommendations during pregnancy. Further testing in a fully powered clinical trial is warranted. Trial registration NCT05093842 on clinicaltrials.gov